A FACILE METHOD FOR 2-THIOPHENACYLIDENETHIAZOLINE DERIVATIVES - KIM, SH; KIM, K; KIM, J; KIM, K; KIM, JH (HETERO CORPORATION, 1993)
The reactions of 2-alkyl-5-phenylisothiazole-3-thiones with 2-chloro-1,3-dicarbonyl compounds in chloroform gave the corresponding isothiazolium chlorides which, upon treatment at room temperature with sodium borohydride in a mixture of chloroform and ethanol, underwent S-N bond cleavage to give 3-alkyl-4,5-disubstituted-2-thiophenacylidenethiazolines. Similarly, treatment of the isothiazolium chlorides with triphenylphosphite in chloroform at 60-degrees afforded the same thiazoline derivatives.